Design and Implementation of a Vibration Analysis Tool - Abughannam, Sahar (My University, 2008)
This thesis work presents the software development stages for a vibration analysis tool developed for a company that produces mining machinery and is interested in monitoring their machines' behaviour. The developed application contributes directly to the field of vibration analysis which is widely applied in many areas nowadays. Such areas include in addition to the mining industry, the automotive industry, and other industries producing rotating machinery. The application developed interfaces with a device designed to acquire vibration data through a three axis acceleration sensor. The device then sends the data wirelessly via Bluetooth technology to a computer on which the application is running. The application then processes the data by applying signal conditioning functions on it. These functions include filtering, Fast and Fourier Transforms. Plots are then generated in order to monitor the machine's behaviour. Additionally, the unfiltered data is logged into a file which allows for playing it back for a more in depth analysis in the future. The application also provides a reporting system that generates reports providing a summary of the machine's behaviour and recommendations for adjusting the machine in order to obtain a better performance. This application provides the company with a reliable and practical way of monitoring their machines, and acts as a solid base for future research that could involve diagnostics and control.
Keywords: Design; Implementation; Vibration; Analysis; software development; mining machinery